In Vitro Antibacterial and Antiproliferative Potential of Echinops lanceolatus Mattf. (Asteraceae) and Identification of Potential Bioactive Compounds - Armel Jackson Seukep; Yong-Li Zhang; Yong-Bing Xu; Ming-Quan Guo (MDPI AG, 2020)
Many species belonging to the genus Echinops are widely used in traditional medicine to treat infectious diseases and cancers. The present study aimed to evaluate the antibacterial and antiproliferative properties of Echinops lanceolatus Mattf. (Asteraceae). The activity of the methanolic extract and subsequent partition fractions was investigated against drug-resistant bacteria (Gram-negative and Gram-positive) and human tumor cell lines using broth microdilution and sulforhodamine B (SRB) assay, respectively. Our findings revealed weak to moderate antibacterial activities of tested extracts, with the recorded minimal inhibitory concentrations ranging from 256 to 1024 µg/mL. The ethyl acetate fraction (EL-EA) was found to be the most effective. Likewise, that fraction displayed strong antiproliferative potential with recorded IC50 of 8.27 µg/mL and 28.27 µg/mL on A549 and HeLa cells, respectively. An analysis based on the ultra-performance liquid chromatography-electrospray ionization tandem mass spectrometry (UPLC-ESI-MS/MS) of the EL-EA fraction allowed the identification of 32 compounds, of which quinic acid and derivatives, cinnamic acid derivatives, dihydrokaempferol, naringenin-7-O-glucoside, apigenin-7-O-d-glucoside, naringin, apigenin, rhoifolin, coniferyl aldehyde, and secoisolariciresinol are well-known compounds of biological importance. This study is first to report on the biological activity and phytochemical profile of E. lanceolatus. We provide a baseline to consider E. lanceolatus as a valuable source of anti-infective and antiproliferative agents.